Optimization of the Multi-element Synthetic Transmit Aperture Method for Medical Ultrasound Imaging Applications - TASINKEVYCH, Yuriy; TROTS, Ihor; NOWICKI, Andrzej; LEWANDOWSKI, Marcin (Archives of Acoustics, 2013)
The paper presents the optimization problem for the multi-element synthetic transmit aperture method(MSTA) in ultrasound imaging applications. The optimal choice of the transmit aperture size is made asa trade-off between the lateral resolution, penetration depth and the frame rate. Results of the analysisobtained by a developed optimization algorithm are presented. The maximum penetration depth andlateral resolution at given depths are chosen as optimization criteria. The results of numerical experimentscarried out in MATLABr using synthetic aperture data of point reflectors obtained by the FIELD IIsimulation program are presented. The visualization of experimental synthetic aperture data of a tissuemimicking phantom and in vitro measurements of the beef liver performed using the SonixTOUCHResearch system are also shown.